2(-6+m)=-22

Simple and best practice solution for 2(-6+m)=-22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(-6+m)=-22 equation:


Simplifying
2(-6 + m) = -22
(-6 * 2 + m * 2) = -22
(-12 + 2m) = -22

Solving
-12 + 2m = -22

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 2m = -22 + 12

Combine like terms: -12 + 12 = 0
0 + 2m = -22 + 12
2m = -22 + 12

Combine like terms: -22 + 12 = -10
2m = -10

Divide each side by '2'.
m = -5

Simplifying
m = -5

See similar equations:

| 2n+n+101+75=360 | | 25x^2+16y^2+100y=384 | | 39+97+n=180 | | 6n+7n+20=75 | | 65-x+2=90 | | 2m+9+6m=15 | | x-2/5x-1/6x-1/3x=1/4 | | 9x-6=21x-30 | | 4x-7=7(x-4) | | M^(2/5)*m^(1/5) | | F(x)=8x^2-10x+2 | | 2y-x-7=0 | | 4(2p+4)=40 | | 4t^2=12t-9 | | x-(.65x)=24.5 | | 10(x+3)=120 | | -4x+9=2x+57 | | x+62=57 | | 53+x=50 | | -8x+1=4x+9 | | 5(x+1)=6x+8 | | 5(x-1)=6x+8 | | 7/2x-11/2=17/2 | | 1.3=x^2+0.3 | | 9+3(x-2)=9-4(x-9) | | 1.4q-6.1q+1.4=-26.8 | | 2(x+2)+x=2(x+1)+1 | | 1.4q-6.1+1.4=-26.8 | | 9+2cosx=10 | | r=Ct+a | | m^2-7.5=92.5 | | 7/5y=26/15 |

Equations solver categories